2017
DOI: 10.4209/aaqr.2017.02.0083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atmospheric Flow Conditions on Fine Aerosols in Sydney, Australia

Abstract: We apply a simple objective measure of an airshed's degree of ventilation and determine the impact on PM 2.5 observations at Lucas Heights, Sydney, Australia. We extend the analysis of previous studies, which considered total PM 2.5 , by: using positive matrix factorisation to split the aerosol mass by source type; and using Radon-222 measurements as an independent indicator of ventilation and mixing. For this coastal airshed we found that for 64% of the time, conditions could be classified into four categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although Sydney's most extreme pollution events are often associated with fires and dust storms (e.g., [28,[50][51][52]), studies analysing the sources of PM 2.5 and NO X in NSW concluded that motor vehicle exhaust was the largest contributor to total NO X [53] and the largest anthropogenic contributor to total PM 2.5 [54]. Power stations are also implicated as a major source of atmospheric fine particles [18].…”
Section: Major Anthropogenic Sources Of Air Pollutionmentioning
confidence: 99%
“…Although Sydney's most extreme pollution events are often associated with fires and dust storms (e.g., [28,[50][51][52]), studies analysing the sources of PM 2.5 and NO X in NSW concluded that motor vehicle exhaust was the largest contributor to total NO X [53] and the largest anthropogenic contributor to total PM 2.5 [54]. Power stations are also implicated as a major source of atmospheric fine particles [18].…”
Section: Major Anthropogenic Sources Of Air Pollutionmentioning
confidence: 99%
“…Recently, few studies show that SB events are associated with an increase of PM1 and PM2.5 concentrations (Babu et al, 2016;Crawford et al, 2017;Piazzola et al, 2012;Rodríguez et al, 2008) most probably due to the production of new ultrafine particle formation events, that seem to take place over the sea, being transported back to the coast.…”
Section: Introductionmentioning
confidence: 99%
“…RF was developed to characterize the characteristics of horizontal transportation in the atmosphere (Allwine and Whiteman 1994), which has been used to quantify coastal recirculation over the Mediterranean basin and the results showed that O 3 concentrations are high for both high and low recirculation (Levy, Dayan, and Mahrer 2008). Many studies showed that the air quality was poor when significant recirculation was observed (Chen et al 2016;Crawford et al 2017;Russo et al 2016;Wu et al 2013). SE was first used to depict the atmospheric vertical diffusion ability and has been proved to be a useful tool for prediction of air quality (Shang et al 2001).…”
Section: Introductionmentioning
confidence: 99%